Optimization of Blended Guava and Fluted Pumpkin Leaves Extract as Corrosion Inhibitor of Mild Steel in 0.5 m Hydrochloric Acid (Nigerian Journal of Technology, 2021)
There are many plant extracts that have been studied for possible use as corrosion inhibitors in the oil and gas industries. Hence, this work is focused on optimization of blended Guava and Fluted Pumpkin Leaves extract as corrosion inhibitor of mild steel in HCI using Weight loss method. Response Surface Methodology of Design Expert trial version 12 StatEase was used to design and analyze the result of the 35-run experiments. Three- factor-three level was adopted in the design. Time, Temperature and Inhibitor Quantity were the independent variables, while the acid concentration of 0.5M was constant throughout the experiments and Inhibition Efficiencies were measured using IE formula. Intervals of 1 hr, 0.2g, and 10C were chosen for the immersion time, inhibitor quantity and temperature, respectively. Phytochemical analysis carried out on the Guava and Fluted Pumpkin Leaves shows that each leaf extract contains phytochemicals which are responsible for inhibiting corrosion. Weight loss result shows that the Blended extract reduces the corrosion rate of mild steel in 0.5MHCI. Additionally,4 experiments for Blended Extract, Fluted Pumpkin, Guava Extract and Industrial Inhibitor were carried out at optimal conditions as predicted by the software at time 4.036 hr, temperature 49.5C , inhibitor quantity 0.487g and ratio of 59.21GE:FP40.79 Inhibition Efficiencies of the Blended, Fluted Pumpkin, Guava Extracts and Industrial Inhibitor were 93.70%, 78.14%, 63.7% and 95.18%, respectively. The results show that the blended and Industrial Inhibitor compared well with the software predicted IE of 96.085%. Therefore, the blended extract could serve as good substitute to the industrial inhibitor.http://dx.doi.org/10.4314/njt.v40i3.6